Inflammation—the role of TRPA1 channel - Yao, Kaifang; Dou, Baomin; Zhang, Yue; Chen, Zhihan; Li, Yanwei; Fan, Zezhi; Ma, Yajing; Du, Simin; Wang, Jiangshan; Xu, Zhifang; Liu, Yangyang; Lin, Xiaowei; et al. (Frontiers in Physiology, 2023)
Recently, increasing numbers of studies have demonstrated that TRP ankyrin 1 (TRPA1) can be used as a potential target for the treatment of inflammatory diseases. TRPA1 is expressed in both neuronal and non-neuronal cells and is involved in diverse physiological activities, such as stabilizing cell membrane potential, maintaining cellular humoral balance, and regulating intercellular signal transduction. TRPA1 is a multi-modal cell membrane receptor that can sense different stimuli, and generate action potential signals after activation via osmotic pressure, temperature, and inflammatory factors. In this study, we introduced the latest research progress on TRPA1 in inflammatory diseases from 3 aspects. First, the inflammatory factors released after inflammation interacts with TRPA1 to promote inflammatory response; second, TRPA1 regulates the function of immune cells such as macrophages and T cells; it has anti-inflammatory and antioxidant effects in some inflammatory diseases. Third, we summarized the application of antagonists and agonists targeting TRPA1 in the treatment of some inflammatory diseases.